Improving the Quality of Islamic Religious Education in the Era of Society 5.0 - Wahyuni, Nur (Proceeding International Conference on Religion, Science and Education, 2022)
Islamic religious education is one of the mandatory materials for students. Islamic Religious Education contains an explanation of creed, Sharia, and morals as well as exemplary taught to foster students to become good Muslims. The delivery of PAI material has been running smoothly and normally. However, the current phenomenon is the Covid-19 pandemic which requires the learning process to be shifted from normal face-to-face or conventional learning to online learning. But as time goes by, the Covid-19 pandemic has begun to recede, so I dared to do offline learning (outside the network) by looking at the conditions that were deemed safe enough to hold face-to-face meetings.